Assessment of renal outcome following therapy in monoclonal immunoglobulin deposition disease: Emphasizing the need for a consensus approach. Issue 3 (1st January 2023) - Pianko, Matthew J.; Tiutan, Timothy; Derkach, Andriy; Flynn, Jessica; Salvatore, Steven P.; Jaffer‐Sathick, Insara; Rossi, Adriana C.; Lahoud, Oscar; Hultcrantz, Malin; Shah, Urvi A.; Maclachlan, Kylee; Chung, David J.; et al.
Abstract: Monoclonal immunoglobulin deposition disease (MIDD), often associated with plasma cell dyscrasias, predominantly affects the kidneys. In this disease, hematologic response (HR) to treatment can be reliably assessed by International Myeloma Working Group (IMWG) consensus criteria, while uniform criteria for assessing renal response are lacking. We report a retrospective analysis of renal outcomes among 34 patients with MIDD. With most patients treated with bortezomib and autologous stem cell transplantation, 26 of 28 (94%) achieved very good partial HR or better. We demonstrate that both IMWG (based on estimated glomerular filtration rate, eGFR) and amyloid (based on proteinuria) criteria are needed to capture renal response: among 28 evaluable patients, 6 (21%) had isolated proteinuria, while 13 (46%) had isolated decreased eGFR. Using both criteria, which were concordant in patients with both decreased eGFR and proteinuria, 22 of 28 patients (79%) achieved a renal response, including 2 of 7 discontinuing dialyses. All 6 patients (100%) with isolated proteinuria and 7 of 13 (54%) with isolated decreased eGFR achieved renal response, suggesting that isolated proteinuria is an early manifestation of MIDD associated with reversible renal damage. Baseline eGFR predicted renal response ( p  = .02 by quartile) and survival ( p  = .02), while HR (CR vs. non‐CR) did not, probably because of high HR rate. With a median follow‐up of 110 months, the median overall survival was 136 months (95% CI: 79–NR) and median renal survival had not been reached. Prospective studies using uniform renal response criteria are needed to optimize the management of MIDD.